2012
DOI: 10.1016/j.jbiomech.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Injectable calcium phosphate cement for augmentation around cancellous bone screws. In vivo biomechanical studies

Abstract: a b s t r a c tIn lower cancellous apparent bone density, it can be difficult to achieve adequate screw fixation and hence stable fracture fixation. Different strategies have been proposed, one of them is through augmentation using calcium phosphate cement in the region at or close to the screw thread itself. To support the hypothesis of an improved screw fixation technique by augmentation of the bone surrounding the implanted screw, in vivo biomechanical and densitometric studies are performed on rabbit speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Unfavourable outcomes include connective tissue formation around the implant, which can affect the long-term anchorage of the implant by delaying formation of a mature bone interface [5,7,17,18]. To date, the optimal cutting criteria to minimize thermal necrosis and apoptosis and to synergistically enhance tissue regeneration by inducing mineralization are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Unfavourable outcomes include connective tissue formation around the implant, which can affect the long-term anchorage of the implant by delaying formation of a mature bone interface [5,7,17,18]. To date, the optimal cutting criteria to minimize thermal necrosis and apoptosis and to synergistically enhance tissue regeneration by inducing mineralization are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of these results led to a re-examination of data already published (Larsson et al, 2012) for an in vivo animal study. This study has shown the general advantage of using calcium phosphate cement in screw augmentation in animals, but further analysis revealed individual results, at 1, 5 and 10 days, that again contradicted the general result.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally regarded as beneficial in its use with both cancellous and cortical screws (Gefen, 2002;Gausepohl et al, 2001). Particularly, Larsson et al (2012) have shown that bone augmentation using calcium phosphate cements in a lapine in vivo model gives significantly improved pullout strength. As a result it might be expected that augmentation with cement should always improve fixation, and consequently improve surgical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Besides bone augmentation, ceramic cements have also been used for screw augmentation [99][100][101][102]. Some results are very promising [103,104], but more data are needed to assess the long-term success of this approach.…”
Section: Cementsmentioning
confidence: 99%